Magnetic susceptibility distribution in the soils of Pune Metropolitan Region: implications to soil magnetometry of anthropogenic loading - Sangode, S.J.; Vhatkar, K; Patil, S.K.; Meshram, D.C.; Pawar, N.J.; Gudadhe, S.S.; Badekar, A.G.; Kumaravel, V. (My University, 2010)
Based on established linkages between ferrimagnetism and heavy metal concentration of anthropogenic particulates, we attempt here to delineate pollutant residing domains and study the role of surface runoff and wind circulations over its redistribution in the Pune Metropolitan Region (PMR) in Maharashtra. A total of 118 samples collected in a ~3 × 3 km grid during pre- and post-monsoon seasons for surface soils, bedrock, dust and rainwaters were analysed for magnetic susceptibility (χlf) and the isothermal remanent magnetization (IRM). The χlf in the soil profiles decrease from bedrock to intermediate soil horizons but notably increase towards top. Spatial variations based on the fundamental rock magnetic parameters (χlf and their frequency dependency (χfd), saturation IRM, demagnetization ratio) and knowledge of the polluting sources show significant anthropogenic loading for the topsoils. The study further reports remarkable postmonsoon changes in all the parameters controlled by surface run-off due to slope variation which appears to be the most effective mechanism of redistribution and dumping the topsoils loaded with anthropogenic particulate matters. Distribution of χfd% further infers wind as another important agent for dispersal of finer ferrimagnetic particulate matters predominantly controlled by the topography amongst other meteorological factors. Additional data for succeeding years would help in modelling the redistribution sensitivity and heavy metal residence effect for the topsoils and sediments in the PMR region.
Keywords: Magnetic susceptibility distribution; Soil magnetometry; Anthropogenic; Pune Metropolitan Region (PMR)